2015
DOI: 10.1016/j.jvs.2014.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic application of contrast-enhanced ultrasound and low-dose urokinase for thrombolysis in a porcine model of acute peripheral arterial occlusion

Abstract: In this experimental pilot study, the addition of contrast-enhanced US accelerated the thrombolytic effect of low-dose intra-arterial thrombolysis in peripheral arterial occlusions. Further clinical studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Activated platelets are targeted and bound to RGDS-modified liposomes, resulting in platelets aggregation 27 , suggesting the feasibility of developing a delivery system of platelet-targeted anti-thrombogenic drug. Studies on thrombolysis by ultrasound combined with microbubble contrast agent and urokinase has been proven in animal models to be a better alternative therapy to drug alone or surgical intervention 28 . Nevertheless, the mechanisms of the thrombolysis therapy and in vivo histological changes are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Activated platelets are targeted and bound to RGDS-modified liposomes, resulting in platelets aggregation 27 , suggesting the feasibility of developing a delivery system of platelet-targeted anti-thrombogenic drug. Studies on thrombolysis by ultrasound combined with microbubble contrast agent and urokinase has been proven in animal models to be a better alternative therapy to drug alone or surgical intervention 28 . Nevertheless, the mechanisms of the thrombolysis therapy and in vivo histological changes are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, research data have emerged advocating the combined use of contrast-enhanced ultrasound (CEUS) and thrombolysis in the treatment of peripheral arterial thrombosis. In an experimental study by Ebben and colleagues [Ebben et al 2015], the addition of CEUS accelerated the thrombolytic effect of low-dose intra-arterial thrombolysis in peripheral arterial occlusions. The contrast agent consists of microsized gas-filled bubbles that collapse when exposed to ultrasound, causing destabilization of the clot and making the clot surface more susceptible to fibrinolytics [Acconcia et al 2014].…”
Section: Major Trialsmentioning
confidence: 99%
“…The improvement of specificity of the thrombolytic agents is a way to overcome the drawbacks of the rt-PA or uPA treatment. Many studies showed that entrapment of the proteins into a delivery system like liposomes could benefit the thrombolysis primarily resulting from the prolongation of circulation duration and the capacity of endowing passive or active targeting ability [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] . Among them, ultrasonic (US) induced delivery of thrombolytic proteins using microbubbles has demonstrated promising properties for site-specific release of payloads from the carrier through cavitational effects and acoustic radiation force on the carrier [21] .…”
Section: Introductionmentioning
confidence: 99%